Gibt es eine neue Kopfspeicheldrüse? – Eher nicht! - Guntinas-Lichius, Orlando; Ihrler, Stephan; Freesmeyer, Martin; Guehne, Falk; Kluge, Regine; Bräuer, Lars; Iro, Heinrich; Paulsen, Friedrich; Dietz, Andreas; Bechmann, Ingo (Laryngo-Rhino-Otologie, 2020)
In October 2020, the lay press, but also some medical journals and websites reported the putative discovery of a new salivary gland in the nasopharynx based on prostate-specific membrane antigen positron emission tomography computed tomography (PSMA-PET/CT) examinations. As an interdisciplinary group from the fields of anatomy, pathology, nuclear medicine and otorhinolaryngology, we come to the view that an accumulation of minor salivary glands has been described here. Minor salivary glands in the nasopharynx and in the peritubar region have been described at least since 1866. The current description in PSMA-PET/CT does not justify the definition of a new, independent salivary gland. The PSMA-PET/CT could, however, be suitable to better protect salivary glands in the nasopharynx when planning radiation therapy. This should be evaluated in clinical trials.
CRIS-Team Scopus Importer:2020-12-04